Reviewing The Contribution And Effectiveness Of Receiving Profit Of Regional Owned Business Entities (BUMD) To Regional Original Income In Kebumen Regency - Desi Susilawati Susilawati; Tri Utami Utami (Proceedings International Conference on Sustainable Innovation (ICoSI), 2021)
The purpose of this study was to determine the level of contribution and effectiveness of profit regional owned Business entities to Regional Original Income in Kebumen District in year of 2016- 2020. The objects used in this study were 3 regional owned Business entities of Kebumen , namely PD BPR Bank Kebumen, PD Apotek Lukulo Kebumen, and PDAM Tirta Bumi Sentosa. This research is quantitative descriptive. This study uses primer data and secondary data. The data were obtained by using documentation techniques, interview and literature study, and the data were analyzed by contribution and effectiveness analysis. The results showed that (1) that PDAM Tirta Bumi Sentosa has an average value of 0.718% ,then PD BPR Bank Kebumen with an average value of 0.563% in And PD Apotek Lukulo Kebumen gave the lowest contribution with an average value of 0.058% and all of them included in the very poor category.This occurred due to an increase in the cost of allowance for productive assets as a result of credits with bad collectibility and affected by the condition of the effects of the Covid pandemic. 19 which caused most of the debtors to have difficulty in paying credit installments (2) that regional owned business entities which had the highest average of effectiveness was PDAM Tirta Bumi Sentosa with an average value of 110 ,41% and very effective. Then PD BPR Bank Kebumen has 92.01% in the effective category. And PD Apotek Lukulo Kebumen which is the lowest effectiveness value is 90.80% and is included in the effective category as well. The solutions to improve contribution are internal management making decisions to be adaptive according to needs, responding wisely to external threats by paying attention to improving the quality of products and services, upskilling employees, and focusing on developing businesses to maintain the sustainability of BUMD's business.